A COMPARATIVE PLACEBO, CONTROL CLINICAL EVALUATION OF PHALATRIKADI KWATH IN MADHUMEHA WITH SPECIAL REFERENCE TO DIABETES MELLITUS TYPE2 - *Sonalika Jena; B.B. Khuntia; Kamdev Das (International Journal of Ayurveda and Pharma Research, 2015)
The study was aimed to have a conceptual review of the disease Madhumeha and its treatment in particular to the use of an herbal drugâ€ Phalatrikadi Kwathâ€ and to compare its efficacy with the control drug (metformin) and placebo through scientific parameters in a double blind clinical control trial. Madhumeha, also known as Diabetes Mellitus is one of the types of Vataja prameha, that has been considered as an incurable disease (Mahagada). Due to indulgence in etiological factors it results in the incomplete formation of Kapha and Meda which further proceeds downward through the channels of Mutravaha srotas and get localized at Basti mukha leading to the symptoms like Prabhoota mutrata (polyurea), Avila mutrata (tubidity of urine) etc. As the disease is Chirakari, it requires an effective treatment which can be continued for a long time without any ill effects. Among the many treatment measures mentioned, Phalatrikadi kwath has been selected in this study and the effect was evaluated. The clinical study includes 50 patients of either sex between 30-60 years of age with Madhumeha (Type2 Diabetes Mellitus) were recruited having range of blood sugar (fasting 126-180 mg/dl, postprandial sugar, 200-250 mg/dl) attending the OPD of G.A.M Puri, Odisha and were divided into three groups. Group I (30 patients) were treated with trial drug (Phalatrikadi kwatha), Group II (10 patients) were treated with control drug (Metformin) and Group III (10 patients) were treated with placebo. All the three groups were recommended with uniform classically described diet (Ahara) & regimen (Vihara). Patients were evaluated in an interval of 15 days for one month. FBS, PPBS with clinical sign & symptoms were assayed. After evaluating the total effects of the treatment, it was observed that Phalatrikadi kwath along with diet and regimen gave satisfactory relief in comparison to control drug (metformin)which is an established drug.